Двухкаскадные модули на основе Bi2Te3 и SiGe для термоэлектрических генераторов - Mikhailovsky, V. Ya.; Bilinskiy-Slotylo, V. R. (PE "Politekhperiodika", Book and Journal Publishers, 2013)
The results of the designing and investigation of cascading modules for direct conversion of high-grade waste heat into electrical energy are presented. The heat and geometrical parameters of cascade branches of the modules based on Bi2Te3 and SiGe are defined. The paper presents design of two-stage modules with electric power 30 and 60 W, as well as experimental results on such modules.